PERENCANAAN EVALUASI PEMBELAJARAN TERHADAP PENGEMBANGAN SEKOLAH - M. Arif Pratama Manurung; Maulana Yontino; Afrida Yanti; Ezra Aisaura; Maya Masita; Inom Nasution (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Learning evaluation is important for an educational institution. With the evaluation, it is hoped that new ideas will emerge from the deficiencies that occur in the field. An evaluation that goes well will be able to provide good development to educational institutions. This study aims to find out how learning evaluation planning is related to school development. This study used the method of literature review (library research). The research results concluded that evaluation planning has a very important influence on implementation in the field. Without a structured plan, the purpose of the evaluation will not be achieved effectively or efficiently. Therefore, it should pay attention to what is the basis or planning in conducting an evaluation. That way, it is hoped that later it will be able to answer what are the obstacles, challenges, and obstacles to learning, both from the teacher and the students themselves.